UPAYA MENINGKATKAN KETERAMPILAN BERMAIN DRAMA MELALUI TEKNIK PEMBELAJARAN ROTATING ROLES SISWA KELAS VIII C SMP NEGERI SUNGAI JAUH TAHUN PELAJARAN 2019/2020 - Elya Martini (JURNAL PERSPEKTIF PENDIDIKAN, 2020)
The purpose of this Classroom Action Research is to find out how rotating role learning techniques canimprove the drama playing skills of VIII C grade students of Sungai Jauh Middle School. This research is aclassroom action research conducted in two cycles. Each cycle consists of four stages, namely: (1) planning,(2) implementation, (3) observation, and (4) reflection. The instruments used in this study were field notes,observation sheets, questionnaires, and assessment sheets. Data analysis was performed using qualitativedescriptive techniques supported by quantitative data. The results showed that the use of the rotating roleslearning technique was able to improve the drama playing skills of students in class VIII C of Sungai RemoteMiddle School. Based on the field notes and observational guidelines, there was a change in students'positive direction. Improved drama playing skills can be seen from two things, namely the success of theprocess and the product. The success of the process can be seen from the changes in students' attitudes after the action implementation is held, students are more active, enthusiastic, have the courage to expressopinions, and are able to work with other students. The success of the product is seen from the playingpractice tests. "The average value of playing student drama before implementing the action is 49.46, cycle I"is 63.5 and in cycle "II is 78.14." The data shows that the drama playing skills of students from pre-action tocycle II has increased by 28.68. Some aspects that show the most significant improvement are aspects ofexpression, motion, and intonation.